2017
DOI: 10.1016/j.jclepro.2017.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of some browse tree leaves on gas production and sustainable mitigation of CH4 and CO2 emissions in dairy calves at different age

Abstract: a b s t r a c tThe present context was aimed to determine the in vitro gas production (GP), mitigation of methane (CH 4 ) and carbon dioxide (CO 2 ) emission, and ruminal fermentation from nine different tree leaves as suitable alternatives for alfalfa hay. Tree leaves and alfalfa hay were incubated with rumen inoculum from calves at different ages (20, 40, and 60 d). The level of asymptomatic GP [mL/g dry matter (DM)] differed (P < 0.05) between different tree leaves compared with alfalfa hay. Most of the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 27 publications
1
4
0
1
Order By: Relevance
“…Furthermore, the breakdown of long chain polysaccharides could have been positively affected by the presence of anthraquinones, which is present at varying proportions in all the medicinal plants used in this study, as previously noted [2]. Both AZ and MO extracts have been reported to equally improve feed digestibility at moderate doses [31]. Furthermore, improved digestibility of the substrate has been associated with the presence of azadirachtin in AZ and the high concentration of alkaloids in MO [32].…”
Section: Resultssupporting
confidence: 66%
“…Furthermore, the breakdown of long chain polysaccharides could have been positively affected by the presence of anthraquinones, which is present at varying proportions in all the medicinal plants used in this study, as previously noted [2]. Both AZ and MO extracts have been reported to equally improve feed digestibility at moderate doses [31]. Furthermore, improved digestibility of the substrate has been associated with the presence of azadirachtin in AZ and the high concentration of alkaloids in MO [32].…”
Section: Resultssupporting
confidence: 66%
“…A subset of the studies has also given a little attention to natural gas production and gross domestic product (GDP) relationship and found two outcomes. One stand of the literature found a positive link between gas production and gross domestic product, supporting the resource blessing phenomenon (Peach and Starbuck, 2011;Diugwu et al, 2013;Bilgili et al, 2020) while the other strand of literature found that natural gas production is associated with adverse outcomes especially Co 2 emission, supporting the resource curse hypothesis (Elghandour et al, 2017;Shearer et al, 2014). Although our study is related to these studies, we use four different estimation strategies to ensure that our findings are more robust and reliable compared to these studies that used a single approach.…”
Section: Introductionmentioning
confidence: 56%
“…, 2013; Bilgili et al. , 2020) while the other strand of literature found that natural gas production is associated with adverse outcomes especially Co 2 emission, supporting the resource curse hypothesis (Elghandour et al. , 2017; Shearer et al.…”
Section: Introductionmentioning
confidence: 64%
“…It should also be noteworthy that in order to utilize unconventional feedstuffs as feed ingredients for ruminant, those byproducts need to be not only highly nutritive to livestock but also nonnutritious to humans. Recently, calcium malate [10], organic acid salts [19], Salix babylonica extract [20], and browse tree leaves [21] were successfully implied in the feeding diets of livestock to investigate their biogas mitigation attributes. However, to the best of our knowledge, there is no study reported on the potent role of E. coli supplementation on the biogases mitigation from various concentrations of PC flour.…”
Section: Discussionmentioning
confidence: 99%